Design of a high linear and ultra-wideband LNA using post distortion star feedback method. (January 2021) - Veisi, Siamak; Yargholi, Mostafa
Abstract: In this paper, a CMOS low noise amplifier (LNA) with very high linearization for ultra-wideband (UWB) applications is presented. In the proposed LNA, both second- and third-intercept points (IIP2 and IIP3) are improved by the new suggested post distortion star feedback (PDSF) technique in a wide frequency range. The star feedback circuit consists of three resistors that eliminate the nonlinear effect of the cascade transistor, and the PD circuit has an auxiliary transistor that eliminates the third-order non-linear coefficient of the main transistor. The post-layout simulation results of the proposed UWB LNA, which is designed using TSMC RF CMOS 65 ​nm, show the maximum power gain of 11 ​dB, minimum NF of 3.2 ​dB, and average IIP3 of 24 dBm in the frequency range of 3.1–10.6 ​GHz. In the designed circuit, the maximum IIP2 of 23.4 dBm is achieved. The chip area of the circuit is 0.874 ​mm 2, while the LNA consumes 15 ​mW from a 1.2 ​V supply voltage.